1997
DOI: 10.1530/eje.0.1370154
|View full text |Cite
|
Sign up to set email alerts
|

Impaired vasopressin suppression and enhanced atrial natriuretic hormone release following an acute water load in primary aldosteronism

Abstract: The release of arginine vasopressin (AVP) and atrial natriuretic hormone (ANH) and their involvement in renal water and electrolyte metabolism in primary aldosteronism in humans were studied. An oral acute water load (20 ml/kg body weight) was given to each of 12 patients before and after surgical removal of their aldosterone-producing adenoma(s). Plasma AVP and ANH were measured simultaneously, and renal water and electrolyte metabolism and tubular functions were determined. The same water load was given to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
(20 reference statements)
1
1
0
Order By: Relevance
“…In this model of hypertension, the release of AVP is elevated, pressor responsiveness to AVP is increased, and AVP antiserum reduces mean arterial blood pressure (16). Consistent with these findings, we recently found that the suppression of AVP was impaired after water load in patients with primary aldosteronism (17). During glucocorticoid excess, on the other hand, AVP may play a minor role in the blood pressure increase, since glucocorticoids inhibit AVP bio- synthesis and secretion as shown in this and other studies (3, 4), Consequently, other systems, including the renin-angiotensin unit, may be responsible for glucocorticoid-induced hypertension (1, 2).…”
Section: Discussionsupporting
confidence: 65%
“…In this model of hypertension, the release of AVP is elevated, pressor responsiveness to AVP is increased, and AVP antiserum reduces mean arterial blood pressure (16). Consistent with these findings, we recently found that the suppression of AVP was impaired after water load in patients with primary aldosteronism (17). During glucocorticoid excess, on the other hand, AVP may play a minor role in the blood pressure increase, since glucocorticoids inhibit AVP bio- synthesis and secretion as shown in this and other studies (3, 4), Consequently, other systems, including the renin-angiotensin unit, may be responsible for glucocorticoid-induced hypertension (1, 2).…”
Section: Discussionsupporting
confidence: 65%
“…In essential hypernatremia, altered regulation of AVP secretion in response to plasma sodium concentration has been reported in some patients. 14, 15 Kimura and coworkers 16 investigated AVP secretion in response to changes in plasma osmolality in patients with primary aldosteronism, in which condition ENaC function is considered to be promoted. The results demonstrated altered regulation of AVP secretion, which was normalized after the surgical excision of adrenal tumor.…”
Section: Discussionmentioning
confidence: 99%